2022
DOI: 10.1039/d2ta06652a
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-metal Zr/Ti MIL-173 porphyrinic metal–organic frameworks as efficient photocatalysts towards solar-driven overall water splitting

Abstract: Hydrolytically stable MOFs combining Ti(IV) ions and porphyrin ligands are expected to display outstanding photophysical properties, making them ideal photocatalysts for the overall water splitting reaction under solar light. We...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…7b and, better in the data provided in Table S4, † the amount of evolved O 2 in the gas phase is below that corresponding to the 0.5 stoichiometry expected for ideal overall water splitting, particularly at shorter irradiation times. This fact has been frequently observed in related precedents of OWS using MOFs as photocatalysts [43][44][45] and can be attributed to the operation of various factors having larger contribution at initial reaction times. Among them, the occurrence of 2e − oxidation of H 2 O, building a stationary low concentration of H 2 O 2 that subsequently decomposes to O 2 (the 4e − oxidation product) and saturation of deareated H 2 O by O 2 , much more water-soluble than H 2 , are two major processes to be considered to justify the lower-than-the-stoichiometry O 2 amount measured in the gas phase.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…7b and, better in the data provided in Table S4, † the amount of evolved O 2 in the gas phase is below that corresponding to the 0.5 stoichiometry expected for ideal overall water splitting, particularly at shorter irradiation times. This fact has been frequently observed in related precedents of OWS using MOFs as photocatalysts [43][44][45] and can be attributed to the operation of various factors having larger contribution at initial reaction times. Among them, the occurrence of 2e − oxidation of H 2 O, building a stationary low concentration of H 2 O 2 that subsequently decomposes to O 2 (the 4e − oxidation product) and saturation of deareated H 2 O by O 2 , much more water-soluble than H 2 , are two major processes to be considered to justify the lower-than-the-stoichiometry O 2 amount measured in the gas phase.…”
Section: Resultssupporting
confidence: 55%
“…As it can be observed in Figure 7b and, better in the data provided in Table S4, the amount of evolved O 2 in the gas phase is below that corresponding to the 0.5 stoichiometry expected for ideal overall water splitting, particularly at shorter irradiation times. This fact has been frequently observed in related precedents of OWS using MOFs as photocatalysts [43][44][45] and can be attributed to the operation of various factors having larger contribution at initial reaction times. Among them, the occurrence of 2 e - Regardless these comments, Table S5 in SI summarizes the use of MOF-based photocatalysts for the OWS into H 2 and O 2 .…”
Section: Chemical Science Accepted Manuscriptsupporting
confidence: 55%
“…In this work, the activity of the UiO-66­(Zr)-NH 2 -25@UiO-66­(Ce) photocatalyst (5 mg) was notably higher with the production rates of H 2 and O 2 reaching to 708 and 320 μmol g –1 , respectively, after 22 h. The estimated apparent quantum yield (AQY) using UiO-66­(Zr)-NH 2 -25@UiO-66­(Ce) as photocatalyst for the OWS is 0.034% at 400 nm. For comparison, a mixed-metal Zr/Ti-MIL-173 porphyrin-based MOF exhibited an AQY of 0.11% at 450 nm . Overall, this study shows the possibility of preparing MOF-on-MOF composites based on UiO-66 solids to develop active photocatalysts for the OWS under simulated sunlight irradiation.…”
Section: Resultsmentioning
confidence: 79%
“…In this context, previous studies in the area of photocatalysis using both inorganic semiconductors and MOFs , have shown that the size and shape of the particles determine their energy band diagram. Other factors, including structural defects such as oxygen vacancies in inorganic semiconductors or missing linkers or clusters in MOFs, also influence the resulting energy level band diagram of the solids. Therefore, these are possible explanations for the deviations in energy level diagrams between the UiO-66­(Zr)-NH 2 or UiO-66­(Ce) solids and the MOF-on-MOF composites.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation